Pengaruh Orientasi Kewirausahaan, Inovasi Produk Dan Keuangan Bersaing Terhadap Kinerja Pemasaran Pada Usaha Rumah Makan Yang Terdaftar Di Dinas Pariwisata Kota Ende - Lawi, Ewaldina W.; Langga, Lambertus; Dua Mea, Maria Helena Carolinda (SCIENTIFIC JOURNAL OF MANAGEMENT AND BUSINESS (SJMB), 2021)
This study aims to determine the effect of entrepreneurial orientation, product innovation and competitive advantage on marketing performance. Types of quantitative research. Sampling used simple random sampling, namely all restaurants in the city of Ende as many as 32 respondents. The data analysis technique is multiple linear regression analysis. The results of the t-test show that entrepreneurial orientation and product innovation have a positive and significant effect on marketing performance, while competitive advantage has no positive and significant effect on marketing performance. The results of the F test show that it simultaneously has a positive and significant effect on marketing performance. The results of the coordination test of determination showed that 65.4% was influenced by other factors.